"I will commit to this child as much as I can for the time that they are with me:" A qualitative examination of how foster carer commitment relates to short-term foster care for young children following abuse and neglect. (January 2023) - Turner, Fiona; Kainth, Gary; MacDonald, Sara; O'Connor, Rory; Crawford, Karen; Minnis, Helen
Abstract: Background: Foster carer commitment to the child has been shown to be of paramount importance in young children's recovery and development following abuse and neglect. In Dozier's definition of commitment in the US, there is a focus on both emotional investment in the child and committing to an enduring relationship with the child. How this relates to the routine practice of short-term, temporary, foster care has not been studied. Objective: This is the first qualitative study to explore the drivers of, and barriers to, commitment in short-term foster care within the broader aim of examining whether short-term care is meeting the needs of maltreated young children. Participants & setting: Fourteen foster carers took part in research interviews and five focus groups were conducted with infant mental health professionals. Methods: Interviews and focus group data were subject to qualitative thematic analysis in order to identify patterns of commonality in relation to our research questions. Results: Three broad themes pertain to commitment and the meeting of young children's needs in short-term foster care: Influence, Timescales and Choice in the fostering role. These themes were found to house both drivers of, and barriers to, commitment in short-term care, which are influenced by systemic normalisations of fostering practices. Conclusions: The emotional investment facet of commitment is more alive in the 'psyche' of short-term foster care than commitment to an enduring relationship. A long-term outlook for the child may be an undefined facet of commitment that is more akin with short-term placements.